AN ANALYSIS OF PROFANITY UTTERED BY MALE AND FEMALE INDONESIAN YOUTUBERS - Windy Ariani; Farida Repelitawaty Br. Kembaren (VISION, 2021)
This research aimed at discovering: (1) the types of profanity uttered by male and female Indonesian Youtubers; (2) the reasons for male and female Indonesian Youtubers in uttering profanity in their videos. This research used qualitative method as the research design. The subjects of this research were male and female Indonesian Youtubers whose videos were analyzed to find out the types of profanity and the reasons for using those profanity. The data collection was done by using observation technique and audio-visual digital materials. The data were analyzed by using interactive model proposed by Miles and Huberman which consisted of three steps namely data reduction, data display and conclusion drawing/verification. The findings of this research showed that: (1) there were four types of profanity uttered by male and female Indonesian Youtubers in their videos. The types were expletive, abusive, humorous, and auxiliary profanity, and; (2) there were five reasons for male and female Indonesian Youtubers in using profanity. The reasons were to draw attention, to offend, to convey negative thought, to respond pain or misfortune and to make fun or jokes.